A rare cause of bilateral facial nerve paralysis due to acute otitis media in a 52-year-old man - Santosh Kumar Swain; Alok Das; Sampada Munjal (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2020)
Facial nerve paralysis is a known complication of middle ear diseases such as chronic otitis media. However, it is rarely seen in acute otitis media (AOM). Bilateral facial nerve paralysis is an extremely rare incidence in AOM in an adult patient. As it is a rare clinical entity, the management of this condition is not very well outlined as per the standard guidelines. Aggressive and appropriate treatment in the earliest period helps patients to recover from facial nerve paralysis. Here, we present a case of bilateral facial nerve paralysis in a 52-year-old male with bilateral AOM. Facial nerve paralysis in both sides recovered to normal with appropriate treatment along with myringotomy.